Photocatalytic degradation of naproxen using TiO2 single nanotubes - Sepúlveda, Marcela; Musiał, Joanna; Saldan, Ivan; Chennam, Pavan Kumar; Rodriguez-Pereira, Jhonatan; Sopha, Hanna; Stanisz, Beata J.; Macak, Jan M. (Frontiers in Environmental Chemistry, 2024)
Herein, TiO2 single-tube (TiO2 ST-NT) powders with and without magnetite Fe3O4 nanoparticles (TiO2 ST-NT@Fe3O4NPs) are presented for the first time as excellent photocatalysts for the degradation of one of the most popular non-steroidal anti-inflammatory drugs (NSAIDs), naproxen (NPX). The TiO2 ST-NT powders were synthesized by anodization followed by etching of the double wall, bending, sonication, ultra-centrifugation, and finally annealing at 600°C. A part of the obtained TiO2 ST-NT powders was decorated with Fe3O4 nanoparticles using a simple one-step decoration process. The best photocatalytic performance of TiO2 ST-NT and TiO2 ST-NT@Fe3O4NPs powders was obtained under the white light (6.2 × 10−4 s-1) and the blue light (2.7 × 10−4 s-1), respectively. During NPX photodegradation using TiO2 ST-NT powders, three main NPX transformation products (P1, P2, and P3) were detected. Upon excitation with the blue light illumination, TiO2 ST-NT@ Fe3O4NPs powders exhibited higher performance (∼80%) than TiO2 ST-NT powders (∼23%) within 1 h, resulting in an approximately three times increased photocatalytic rate constant. Moreover, under simulated sunlight conditions, TiO2 ST-NT powders demonstrated remarkable activity, achieving a 94% NPX degradation within 1 h. TiO2 ST-NT and TiO2 ST-NT@Fe3O4NPs powders represent excellent photocatalysts for NPX degradation.